Recent Applications of Carbonaceous Nanosorbents in Solid Phase Extraction for the Determination of Pesticides in Food Samples. (3rd September 2019) - Reinholds, Ingars; Jansons, Martins; Pugajeva, Iveta; Bartkevics, Vadims
Abstract: This article covers recent trends of carbonaceous nanomaterial supported solid phase extraction for the liquid and gas chromatography analysis of pesticides in food samples. Several advanced carbonaceous nanosorbents have been reported over the previous decade for pesticide extraction, such as graphene derivatives modified by combination with silica, amines, polymers, and/or magnetic nanoparticles. The advances in this field have opened possibilities for using neat or modified carbon nanotubes or graphene-type sorbents for the pre-concentration of polar or nonpolar pesticides by solid phase extraction (SPE) or micro-SPE methods or to apply such nanomaterials for the removal of matrix components by dispersive SPE during sample clean-up. The applications of such nanosorbents should increase in the next few years, considering the expected improvements of their properties, including time and resource economy, selectivity, and reusability.